Improved electrocaloric effect in (100)-oriented Pb0.97La0.02(Zr0.57Sn0.38Ti0.05)O3 antiferroelectric thick film by interface engineering - Zhao, Ye; Hao, Xihong; Zhang, Qi (Elsevier, 2015)
In this work, 1.5-μm Pb0.97La0.02(Zr0.57Sn0.38Ti0.05)O3 antiferroelectric thick films with and without a ZrO2 thin layer were deposited on LaNiO3(100)/Si(100) substrates. The effects of ZrO2 thin layer on the microstructure, electrical properties, and especial electrocaloric effect of the antiferroelectric films were studied in detail. Although the films both with and without ZrO2 buffer layer displayed (100)-preferred orientation, possessed dense and uniform surface microstructure, the ZrO2-buffered films have an enlarged grain size by 27%, compared with the thick films without the buffer layer. Accordingly, the dielectric constant and saturate polarization of this antiferroelectric thick films was improved by the insertion of ZrO2 thin layer, and simultaneously its leakage current was slightly reduced. As a result, a great improvement in cooling character caused by ferroelectric–antiferroelectric phase switching, was realized in the ZrO2-buffered films.
Keywords: antiferroelectric; thick films; electrocaloric effect; interface engineering